Câncer Registry of Pernambuco: (1967-1968) - Kruse, Bertoldo (2023)
The “Registro de Câncer de Pernambuco” is in operation since 1967 under the auspices of the following organizations: Serviço Nacional de Câncer do Ministério da Saúde Universidade Federal de Pernambuco Secretaria de Saúde de Pernambuco Sociedade Pernambucana de Combate ao Câncer Faculdade de Ciências Médicas de Pernambuco.